The state of 3D printing of bioengineered customized maxillofacial bone scaffolds: a narrative review - Matheus, Henrique R. [UNESP]; Hadad, Henrique [UNESP]; Guastaldi, Fernando P. S. (AME Publishing Company, 2024)
Background and Objective: Regeneration of oral and maxillofacial defects is of great interest and impacts the lives of many. The search for strategies that mimic the outcomes expected with autologous grafts while overcoming its limitations of limited availability and risk of infection is a growing field in dentistry, and the objective of this research was to provide a narrative review on a promising therapy for improving maxillofacial reconstruction. Methods: A detailed data-based search using PubMed was performed looking for articles in English with the search including the following terms: maxillofacial bone regeneration, tissue engineering, 3D printing, stem cells, scaffolds, and growth factors. The search was supplemented by checking references of relevant review articles. The search was performed on February 10th, 2022. Key Content and Findings: The manufacturing of personalized 3D-printed bioactive scaffolds brought to light the possibility of applying tissue engineering (TE) concepts in a personalized manner for each patient. Imaging is the first step for acquiring personalized information for future data processing, planning, prototyping, and manufacturing of single pieces with the structure and shape desired. It had been shown by preclinical models that carrying undifferentiated cells [mesenchymal stem cells (MSCs)] and growth factors onto these customized 3D-printed scaffolds provides biological support for future translational application of customized bone tissue engineering (BTE). There are still some issues that need to be addressed prior to implementing this therapeutic modality as a daily clinical practice. The biological basis, techniques, limitations, and future perspectives are comprehensively addressed by this review. Conclusions: Surgeons shall be alert to the advances in the field of BTE and 3D printing technologies, be capable of selecting appropriate techniques and materials (relying on the scientific evidence so far) and have the necessary ability for reconstructing oral and maxillofacial bone defects.
Keywords: 3D printing; growth factors; scaffolds; stem cells; Tissue engineering (TE)